Implementation Of The Team Assisted Individualization (TAI) Learning Model To Improve Learning Activities And Outcomes Students - Simarmata, Laura Elsa; Sriwedari, Tuti; Zainal, Andri; Sibarani, Choms Gary Ganda Tua (STABN RADEN WIJAYA WONOGIRI, 2024)
The problem in this study is the low level of student learning activity and the accounting learning outcomes that remain below the Minimum Mastery Criteria (KKM). The purpose of this study is to determine the improvement in learning activity and accounting achievement of students in class XI AKL 2 at SMK Negeri 6 Medan through the implementation of the Team Assisted Individualization (TAI) learning model. This research was conducted at SMK Negeri 6 Medan in the 2024/2025 academic year. The subjects of the study were 35 students from class XI AKL 2, while the object of the study was the Team Assisted Individualization learning model. The study was carried out in two cycles. Data collection techniques included observation sheets to assess student learning activity and tests to measure learning outcomes. The data analysis techniques used were both quantitative and qualitative. Based on the observation sheets, in Cycle I, 12 students (34.29%) were categorized as active and very active. In Cycle II, this number increased to 31 students (88.58%), meeting the success indicator of ≥ 85%. Regarding learning outcomes, the data showed that the average pre-test score was 69.71, with 15 students (42.85%) achieving mastery. In the post-test of Cycle I, the average score increased to 82.00, with 26 students (74.29%) achieving mastery. This improved further in the post-test of Cycle II, with an average score of 95.71 and 33 students (94.29%) achieving mastery, thereby meeting the success indicator of ≥ 85%. Based on this analysis, it can be concluded that the implementation of the Team Assisted Individualization (TAI) learning model can improve both the learning activity and accounting achievement of students at SMK Negeri 6 Medan.